THE INFLUENCE OF OCCUPATIONAL SAFETY SOCIALIZATION ON REDUCING THE INCIDENCE OF WORK ACCIDENTS AT THE KLARI KARAWANG COMMUNITY HEALTH CENTER - Jumaedi, Jumaedi; Chaerani Tri Yuliana; Wieke Widhiantika; Yasin Azhari; Muhidin, Muhidin; Wendi Darmawan (International Journal of Social Science, 2023)
Work accidents in healthcare facilities, such as community health centers (Puskesmas), pose a serious problem that affects the safety and well-being of healthcare workers. This study aims to evaluate the impact of occupational safety awareness programs on reducing the incidence of work accidents at Puskesmas Klari, Karawang. The research uses a quantitative approach with an analytical survey design, involving 50 healthcare workers as respondents using a total sampling technique. Data were collected through validated and reliable questionnaires and analysed using logistic regression to determine the impact of safety awareness on the occurrence of work accidents. The results show that safety awareness programs significantly influence the increase in healthcare workers' awareness, which is followed by a decrease in work accident rates. The "Aware" group saw a 30% increase in awareness after training, and this group experienced a 20% reduction in work accident incidents. The "Somewhat Aware" group also showed a 15% increase in awareness and a 20% decrease in incidents. However, the "Unaware" and "No Response" groups demonstrated lower improvements in awareness and reductions in incidents, with increases of only 5% and 10%, respectively. This indicates that the current awareness programs are still not fully effective for groups with low awareness or those who are apathetic. The conclusion of this study is that comprehensive and continuous occupational safety awareness programs can increase awareness and reduce the incidence of work accidents at Puskesmas Klari. However, developing more varied training programs tailored to the specific needs of healthcare workers is necessary to achieve optimal effectiveness. Evidence-based and participatory safety policies also need to be implemented to strengthen workplace safety practices. This study provides significant contributions to developing occupational safety policies in healthcare facilities in Indonesia